Auditing Industrial Safety Management: A Case Study - Sondre L. Bjelle; Are K. Sydnes (International Journal of Management, Knowledge and Learning, 2019)
As industries are becoming increasingly self-regulatory, external auditing has become increasingly important to ensure that industrial practices are in line with regulations and the public good. This study asks if there is a fit between the industrial practices of safety management and external auditing. It concludes that while companies largely manage safety through operational-level experience and with a low level of formalisation, the audits have a primary focus on formal documentation and gathering audit evidence at the strategic and tactical levels in the organizations. This limits the effectiveness of auditing as a tool both for learning and regulating safety management.